Methadone maintenance treatment and impulsivity: premature responding - Kathrin Weidacker (Journal of Clinical and Experimental Neuropsychology, 2023)
Introduction: Previous research showed that methadone maintenance treatment (MMT) is linked to impulsivity, with higher impulsivity levels being associated with for example, increased drug use. One aspect of impulsivity, most commonly studied in rodent research, is premature responding, the failure to wait for a starting signal. Premature responding is of high translational significance since it predicts the development of addiction-like behaviors in rodents. Methods: We assessed 45 MMT patients and 46 demographically matched (age, sex, education, and handedness) healthy volunteers (HVs) on premature responding alongside action and inhibition of instructed and intentional trials using the Intentional Hand Task (IHT). Results: The results showed markedly enhanced premature responses in the MMT vs. the HV group, which correlated positively with methadone dosage in the MMT patients. Throughout the task, MMT patients were faster across all trial parts and less accurate in response to instructed trials compared to HVs. Conclusions: The increase in premature motor reactions during variable waiting periods alongside increased motion speed and lower accuracy might reflect a specific motor inhibition deficit in MMT, a subcomponent of impulsivity not previously assessed in MMT. Incorporating an experimentally defined measure of impulsivity, such as premature responding, into existing test batteries used by clinicians might enable more tailored treatments addressing the increased impulsivity levels and associated dysfunctional behaviors in MMT.